2013
DOI: 10.4161/epi.25865
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive patterns of DNA methylation associated with Parkinson disease

Abstract: Parkinson disease (PD) is a multifactorial neurodegenerative disorder with high incidence in the elderly, where environmental and genetic factors are involved in etiology. In addition, epigenetic mechanisms, including deregulation of DNA methylation have been recently associated to PD. As accurate diagnosis cannot be achieved pre-mortem, identification of early pathological changes is crucial to enable therapeutic interventions before major neuropathological damage occurs. Here we investigated genome-wide DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
160
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(168 citation statements)
references
References 49 publications
7
160
0
1
Order By: Relevance
“…Concordant DNA methylation profiles in brain and blood samples from the same individuals suggest that blood might hold promise as surrogate for brain tissue to detect DNA methylation. [28][29][30] Genome-wide methylation arrays revealed similar methylation patterns for the HOX genes in breast cancers and white blood cells, which suggests that methylation is more likely to be a normal developmental and tissue-specific process that does not directly relate to the malignant mechanism. 31 Interestingly, functional in silico analysis using the MENT database showed no correlation with gene expression in normal brain and blood tissues for the methylation of 2 HOXB7 promoter CpGs but there is evidence that lower HOXB7 methylation values in brain tightly regulate Figure 3.…”
Section: Discussionmentioning
confidence: 97%
“…Concordant DNA methylation profiles in brain and blood samples from the same individuals suggest that blood might hold promise as surrogate for brain tissue to detect DNA methylation. [28][29][30] Genome-wide methylation arrays revealed similar methylation patterns for the HOX genes in breast cancers and white blood cells, which suggests that methylation is more likely to be a normal developmental and tissue-specific process that does not directly relate to the malignant mechanism. 31 Interestingly, functional in silico analysis using the MENT database showed no correlation with gene expression in normal brain and blood tissues for the methylation of 2 HOXB7 promoter CpGs but there is evidence that lower HOXB7 methylation values in brain tightly regulate Figure 3.…”
Section: Discussionmentioning
confidence: 97%
“…As exemplified in several reviews but particularly in the current one, epigenetic research has been conducted on a number of tissues including postmortem brain samples together with peripheral tissues such as saliva and blood. Epigenetic signatures are known to differ from one tissue to another; nevertheless, recent studies encourage the common assumption of epigenetic hallmarks in blood being replicable in brain tissues (Ewald et al, 2014;Masliah et al, 2013).…”
Section: Where Do We Look?mentioning
confidence: 95%
“…DNA methylation profiles of human hippocampus from AD patients, revealed promoter hypermethylation of the dual-specificity phosphatase 22 (DUSP22) gene, which is a likely candidate gene for the pathogenesis of AD since it determines tau phosphorylation status and CREB signaling (Sanchez-Mut et al, 2014). Distinct changes in DNA methylation patterns have also been observed in patients with PD and ALS (Martin and Wong, 2013; Masliah et al, 2013) and increased global DNA methylation has been suggested as a biomarker for ALS (Tremolizzo et al, 2014). Together, these findings suggest that epilepsy and neurodegenerative conditions may share global changes in the methylome as a consequence of altered adenosine homeostasis.…”
Section: Epigenetic Changes In Epilepsy and Neurodegenerative Disementioning
confidence: 99%